Investigators Authority and Accountability in Pursuing Wanted Persons in Narcotics Cases: A Normative Juridical Analysis of the West Java Regional - Widri Sukandi; Agus Rasyid C W (Green Social: International Journal of Law and Civil Affairs, 2026)
This article examines the authority and accountability of investigators in pursuing individuals listed as wanted persons (Wanted Persons List) in narcotics cases handled by the West Java Regional Police. The study employs a normative juridical method supported by statutory, conceptual, and analytical approaches to evaluate the relationship between coercive investigative powers, procedural legality, and the protection of due process rights. The findings indicate that investigators’ authority originates from statutory attribution under narcotics legislation and criminal procedural law and is exercised through delegation and mandates within the police organizational structure. Nevertheless, the pursuit and arrest of wanted persons must remain subject to legal certainty, administrative accuracy, proportionality, and respect for human rights. Investigators are required to issue valid summonses, maintain complete investigative records, verify the status of individuals listed in the Wanted Persons List, document arrest procedures, apply force only when necessary and proportionate, and obtain judicial authorization for searches, seizures, or asset-related measures. The study concludes that layered internal, judicial, and public accountability mechanisms are necessary to prevent misuse of authority, strengthen professional responsibility, protect suspects’ rights, and ensure that narcotics law enforcement remains effective, transparent, and consistent with the principles of the rule of law.